Impact of traumatic life events on clinical variables of individuals with first-episode psychosis and healthy controls. (February 2023) - Butjosa, Anna; Usall, Judith; Vila-Badia, Regina; Mezquida, Gisela; Cuesta, Manuel J; Rodríguez-Toscano, Elisa; Amoretti, Silvia; Lobo, Antonio; González-Pinto, Ana; Espliego, Ana; Corripio, Iluminada; Vieta, Eduard; et al.
Background: Traumatic life events (TLEs) are one of the most robust environmental risk factors for the onset of first-episode psychosis (FEP). Aims: To explore TLEs in FEP patients and healthy controls (HC), to analyze gender differences and to examine whether TLEs were associated with sociodemographic, clinical and psychofunctional variables in all FEP sample and split by age. Methods: Descriptive and cross-sectional study. Three hundred and thirty-five FEP and 253 HC were recruited at 16 Spanish mental health research centers. The Traumatic Experiences in Psychiatric Outpatients Questionnaire was administered. Results: We found a higher number of TLEs in FEP than in HC, and the proportion of individuals with three or more TLEs was significantly higher in the FEP group. No differences were found in terms of gender and age. There was no relationship between total number of TLEs and psychotic symptomatology and functional outcomes. Conclusions: The number and cumulative TLEs should be taken into account in the detection, epidemiology and process of recovery in FEP.